Layanan Penelusuran Informasi dan Layanan Turnitin Pada PSBB di Perpustakaan Institut Pertanian Bogor dan Perpustakaan Universitas Gadjah Mada - Rita Komalasari; Wahyu Supriyanto (Jurnal IPI (Ikatan Pustakawan Indonesia), 2021)
The world is currently facing a very severe pandemic, namely Covid-19. This has had a negative impact on various aspect of life such as economics, social, culture and so on. Libraries as an information service centres are also affected by the COVID-19. Librarians as information managers must have serious effort so that the user are not negatively affected by the emergence of this pandemic. Or even though it was affected, it did not hamper their studies in finding and obtaining the needed information and library services. The purpose of this study is to analyze library service statistics in terms of information retrieval and Turnitin services as well as to find out the librarian’s strategy in providing services during the pandemic. The method used is quantitative descriptive, comparing library services in 2019 (before the pandemic) with 2020 (during the pandemic), at IPB University and Gadjah Mada Univerity Libraries. The results of a stydy at IPB University Libraries show that there has been an increase in information retrieval services and turnitin services. Likewise, at the Gadjah Mada University Library, online services have been increasing for tracking final works and checking plagiarism by turnitin.